2008
DOI: 10.1007/s11442-008-0455-0
|View full text |Cite
|
Sign up to set email alerts
|

Land use change of Kitakyushu based on landscape ecology and Markov model

Abstract: Based on four phases of TM images acquired in 1990TM images acquired in , 1995TM images acquired in , 2000TM images acquired in and 2005 paper took Kitakyushu in Japan as a case study to analyze spatial change of land use landscape and corresponding effects on environmental issues guided by landscape ecology theory in virtue of combining technology of Remote Sensing with GIS. Firstly, land use types were divided into 6 classes (farmland, mountain, forestland, water body, urban land and unused land) accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 26 publications
(14 reference statements)
0
41
0
2
Order By: Relevance
“…Higher Division values indicate increased fragmentation. The division index in 2014 was larger than that in 2009, which showed that the patch distribution became more dispersed because of the increase in human activities [37].…”
Section: Landscape Indices (Li)mentioning
confidence: 86%
“…Higher Division values indicate increased fragmentation. The division index in 2014 was larger than that in 2009, which showed that the patch distribution became more dispersed because of the increase in human activities [37].…”
Section: Landscape Indices (Li)mentioning
confidence: 86%
“…Meanwhile, the future condition was analyzed by a Markov chain method based on past land covers.Markov chain were used to gain the percentage and probability for each type of land cover convert to other land cover type. A first-order Markov chain model is a model in which probability distribution over next state is assumed to depend only on the current state [18]. A first-order Markov model have been widely used to represent the land cover change for diffrent time intervals.…”
Section: Modeling Of Land Cover Changesmentioning
confidence: 99%
“…However, only a few studies focus on behavioral sequences (Gherardi and Pieraccini, 2004). A behavioral sequence can be modeled through the Markov chain, a discrete random process in which the probability of a system in the next time step depends only on the current state of the system and is independent of the previous step (Guan et al, 2008). The Markov chain has been used to analyze landscape changes (e.g., Baker, 1989), population ecology (e.g., Seneta, 1966;Fujiwara and Caswell, 2002), and behavioral ecology (Lusseau, 2003).…”
Section: Introductionmentioning
confidence: 99%